Year two: the impact of addictions education and the experiential activities on attitudes of students - Balich, Robert; Warren, Jane; Weatherford, Jennifer; Zakaria, Noor Syamilah; Schwede, Diana (Emerald, 2015)
Purpose – The purpose of this paper is to examine the effects of education and experiential learning on counseling student’s perceptions of substance use and counseling those with substance-related problems. Some counselors report having had negative experiences and beliefs about substance use, abuse, and persons with substance related-problems. A counselor’s negative beliefs and experiences can impair their capacities of working effectively and empathetically with persons who seek help for substance abuse problems. Research reports that education can assist helping professionals to be able to work more efficiently with clients with substance abuse struggles by increasing awareness of substance abuse problems, enhancing empathy, increasing professional’s ability to relate with what clients may be experiencing, training in appropriate interventions, and referral skills.